Comparison of Pregnancy Outcomes of Women with and Without Hypertension at the Latent Phase of Labor Who Were Under Medical Care for Preeclampsia - Resul Karakus; Cetin Kilicci; Enis Ozkaya; Ezgi Darici; Onder Tosun; Sultan Seren Karakus; Ali Aras (Gynecology Obstetrics & Reproductive Medicine)
OBJECTIVE: We explored the association between hypertension (>140/90) at the latent phase of labor (resistant hypertension) and the subsequent development of major maternal complications or adverse infant outcomes in women with preeclampsia under medical care.